2021
DOI: 10.1001/jamanetworkopen.2021.27403
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Health Outcomes Among Survivors of COVID-19 Infection 1 Year After Discharge From Hospitals in Wuhan, China

Abstract: IMPORTANCEThe long-term health outcomes and symptom burden of COVID-19 remain largely unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
188
9
14

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(228 citation statements)
references
References 34 publications
17
188
9
14
Order By: Relevance
“… 35 Similar results were obtained by a longitudinal analysis of 2433 patients with antecedent SARS-CoV-2 infection; at 1-year follow-up, the reported neurological symptoms included fatigue (30%), myalgia (8%), dizziness (3%), headache (2%), and taste/smell disorders (1%). 5 In an online international survey of 3762 participants with antecedent COVID-19, however, a much higher prevalence of neurological manifestations affecting the CNS and PNS was reported. 32 In the first 6 months after acute disease, the most frequently reported symptoms encompassed sensorimotor deficits (91%), cognitive dysfunction (85%), emotional/mood disorders (88%), sleep disturbances (79%), headache (77%), memory impairment (73%), and smell/taste disorders (58%).…”
Section: Neurological Manifestations Of ‘Long-covid’ Syndromementioning
confidence: 99%
See 1 more Smart Citation
“… 35 Similar results were obtained by a longitudinal analysis of 2433 patients with antecedent SARS-CoV-2 infection; at 1-year follow-up, the reported neurological symptoms included fatigue (30%), myalgia (8%), dizziness (3%), headache (2%), and taste/smell disorders (1%). 5 In an online international survey of 3762 participants with antecedent COVID-19, however, a much higher prevalence of neurological manifestations affecting the CNS and PNS was reported. 32 In the first 6 months after acute disease, the most frequently reported symptoms encompassed sensorimotor deficits (91%), cognitive dysfunction (85%), emotional/mood disorders (88%), sleep disturbances (79%), headache (77%), memory impairment (73%), and smell/taste disorders (58%).…”
Section: Neurological Manifestations Of ‘Long-covid’ Syndromementioning
confidence: 99%
“… 106 , 109 Discordant findings are also found in the literature concerning the contribution of demographic factors to ‘long-COVID’. With respect to age, for example, although a number of studies support that increasing age confers an increased susceptibility to long-term sequelae, 5 , 40 , 109 other studies reported that younger patients may be at higher risk of ‘long-COVID’. 110 Moreover, a striking prevalence of ‘long-COVID’ symptoms of nearly 43% has been reported in children with antecedent SARS-CoV-2 infection, albeit these prevalence estimates remain debatable.…”
Section: Diagnostic Approach To Neurological ‘Long-covid’ Sequelaementioning
confidence: 99%
“…It should be noted that most studies included samples with <500 participants, were conducted in one single center, included follow-up periods shorter than 12 weeks and did not specifically focus on sex differences [15][16][17][18][19][20][21][22][23][24][25]. Three recent multicenter studies have been published [26][27][28]. Sigfrid et al included 327 hospitalized COVID-19 survivors from five hospitals and reported that females younger than 50 years were two times more likely to report fatigue and seven times more likely to report dyspnea than men of the same age seven months after hospital discharge [26].…”
Section: Introductionmentioning
confidence: 99%
“…This process leads some alveolocapillary units to higher V / Q ratios. While COVID-19 survivors are considered disease-free regarding the acute phase [ 22 ], persistent oxygen desaturation and fatigue are commonly reported in the post-acute period.…”
Section: Discussionmentioning
confidence: 99%